About population density of ungulates in open-air cages - N. .. Ovechkina; V. .. Kozlov (Аграрная наука Евро-Северо-Востока, 2016)
In Russia many scientific and practical questions of open-air cages cultivations of such species of hoofed animals as a maral or a red deer (Cervus elaphus L.), a spotty deer (Cervus nippon L.), a wild boar (Sus scrofa L.), the European fallow deer (Dama dama L.), mouflon (Ovis musimon L.), and roe deer (Capreolus capreolus L.) are studied not enough. The purpose of the given researches is to study influence of population density of hoofed animals in open-air cages on success of animals' reproduction. Within four years features of the maintenance, success of reproduction of a wild boar, a maral, a spotty deer, the European fallow deer, mouflon were studied at open-air cages maintenance in territory of three hunting economy in the Tver' region. It is known that on success of reproduction of natural animals' populations the great influence is rendered by high density of their population causing stress in animals and reducing their annual gain. In studied open-air cages population density of deer fluctuated from 0.08 to 2 animals/ha. Our researches of influence of this factor on reproduction of hoofed animals in conditions of open-air cages maintenance have shown that at a fallow deer the business exit of young growth fluctuated from 0.21 to 0.40 individuals; at a maral from 0.25 to 0.30; at a red deer - from 0.63 to 1.0 individuals per an adult female. Thus the young growth yield changed in direct ratio with population density of animals (r = 0.92). Hence, at an existing level of deer feeding in an open-air cage the density of their population up to 2 animals/ha is not the ecological factor limiting reproduction of animals. In open-air cages it is not observed the stress-factor limiting reproduction though population density repeatedly surpasses density under natural habitat.